Calculate: (2x+5)+(x+1)=3(x-1)+6

Expression: $\left( 2x+5 \right)+\left( x+1 \right)=3\left( x-1 \right)+6$

Remove unnecessary parentheses

$2x+5+\left( x+1 \right)=3\left( x-1 \right)+6$

When there is a $+$ in front of an expression in parentheses, the expression remains the same

$2x+5+x+1=3\left( x-1 \right)+6$

Distribute $3$ through the parentheses


Collect like terms


Add the numbers


Calculate the sum


Cancel equal terms on both sides of the equation


The statement is false for any value of $x$